Variation in use of antipsychotic medications in nursing homes in the United States: A systematic review. Issue 1 (December 2017) - Cioltan, Hannah; Alshehri, Samah; Howe, Carol; Lee, Jeannie; Fain, Mindy; Eng, Howard; Schachter, Kenneth; Mohler, Jane
Abstract Background The use of antipsychotic medications (APMs) in nursing home residents in the U.S. is an increasingly prominent issue and has been associated with increased risk of hospitalization, cardiovascular events, hip fractures, and mortality, among other adverse health events. The Food and Drug Administration has placed a black box warning on these drugs, specifying that they are not meant for residents with dementia, and has asked providers to review their treatment plans. The purpose of this systematic PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses)-based review was to summarize original research studies on facility level characteristics contributing to the use of antipsychotics in nursing homes across the United States, in order to investigate the variation of use. Methods We searched Ovid Medline, Embase, Cochrane Library, Web of Science, CINAHL, PsycInfo, and Sociological Abstracts. Articles were selected according to the following criteria: (1) Population of interest: older adults (≥60 years of age) residing in nursing homes (not home-based or inpatient hospital settings) in the U.S. (2) Receiving APMs, typical and/or atypical. Specifically excluded were studies of psychotropic medications such as antidepressants, benzodiazepines, anxiolytics, hypnotics, mood stabilizers, and stimulants. All study designs were considered, though reviews, editorials, letters to the editor and opinion pieces were excluded. An expert consultant panel was consulted to categorize facility characteristics into domains and determine possible etiologies of APM use based upon each characteristic. Results Nineteen observational studies, both quantitative and qualitative, published from 2000 to 2015, met full inclusion criteria and were included in this review. APM use varied based on multiple facility characteristics across several domains: 1) physical, 2) staffing, 3) occupancy, 4) market, and 5) quality. Conclusions Variation in use of APMs in U.S. nursing homes based upon facility characteristics exemplifies the need for a more systematic protocol guiding the use of these medications, along with heightened regulatory policies and enforcement.